How Social Capital Drives Farmers’ Multi-Stage E-Commerce Participation: Evidence from Inner Mongolia, China - Kewei Gao; Guanghua Qiao (Agriculture)
The development of new e-commerce platforms has become a crucial driver of economic growth in developing countries, driven by the global wave of digitalization and informatization. However, research on e-commerce development in underdeveloped rural areas of China remains scarce, with even less focus on farmers’ e-commerce behaviors. Based on rural China’s unique characteristics, this study conducts a field survey of 346 rural households in Inner Mongolia. Using the Triple-Hurdle and mediation effect models through the lens of social capital, this study examines how social capital and digital literacy influence farmers’ short-term decisions and long-term investments in e-commerce participation across three dimensions: “willingness”, “choice”, and “degree of participation”. The aim is to identify how to leverage social capital as well as digital social literacy to enhance farmers’ e-commerce participation and promote the sustainable development of rural e-commerce. The results show the following: (1) Among the surveyed farmers, 198 households expressed a willingness to engage in e-commerce, 118 households participated, and only 1 household reached a participation level above 50%. This underscores the insufficient e-commerce engagement and ongoing challenges in rural Inner Mongolia. (2) Social capital, as a critical factor, positively affects farmers’ willingness to participate, choice to participate, and degree of participation in e-commerce at the 1% significance level, with regression coefficients of 1.386, 1.202, and 0.119, respectively. Its impact is strongest in the early stages of fostering willingness, followed by its effect on participation choice. However, its influence on the degree of participation diminishes due to the involvement of other complex factors. (3) Social capital enhances farmers’ digital social literacy at the 1% significance level, and digital social literacy plays a mediating role in the process by which social capital influences farmers’ e-commerce behavior. (4) Heterogeneity analysis shows that during actual participation, the impact of social capital on e-commerce behaviors is more pronounced among farmers with smaller household sizes and higher income levels. Based on these findings, this study recommends building social capital across different farmer groups, establishing online information-sharing platforms, and offering tailored technical and digital literacy training for diverse farmer demographics.